Illocutionary Acts on Anies Baswedan’s Speech in Mayoral Meeting Cities Against Covid-19 Global Summit 2020 - Dhani Aprilia Sesanti; Entika Fani Prastikawati; Ajeng Setyorini (SALEE: Study of Applied Linguistics and English Education, 2021)
In this study, the researchers aim at describing illocutionary acts and the most frequently found in Anies Baswedan’s speech dealing with Covid-19. The researchers used a descriptive qualitative method to choose the data. The researcher tends to analyze the data using the pragmatic theory specifically a speech act proposed by Searle (1979) delivered by Anies Baswedan. Illocutionary acts can be divided into 5 types, there are representative, declarative, directive, commissive, expressive. Then, the researchers obtained the data from Anies in Mayoral Meeting Cities Against Covid-19 Global Summit 2020 with the clauses as the data analysis. The result shows that there are 102 data found in the video. Then, the dominant number found is representative with the total number 55 (53,9%), then followed by declarative 22 (21,6%), directive 12 (11,8%), expressive 8 (7,8%), and commissive 5 (4,9%). Then, representative one is dominant since the data tends to deliver the message by reporting, stating, describing a phenomenon, Covid-19 as the issue that must be solved. It is concluded that this study is in the line with the theories and the previous studies dealing with the illocutionary act. On the contrary, there is a previous study that contrasts with this study.